Independence: an introduction to the #AoIR2021 special issue. Issue 6 (26th April 2022) - Kerr, Aphra; Iliadis, Andrew
ABSTRACT: This paper introduces the 'Independence' themed special issue which includes research presented at the 22nd annual Association of Internet Researchers (AoIR) conference (2021). 'Independence' as a special issue theme could hardly be timelier, both in geopolitical and internet research terms. The call for the 2021 AoIR annual conference asked us to reflect on the ambivalence of the term, to look back on historical struggles for independence, the long waves of history, and prompted us to ask who benefits from independence (and who does not). Hosted online for a second year, this time by universities in Philadelphia (USA), the conference was bounded by the Black Lives Matter movement, the insurrectionist storming of Washington, D.C.'s Capitol Hill, and global struggles to control the COVID-19 pandemic. This special issue includes nine papers that showcase new research exploring the affordances offered by digital media platforms to people, users, and workers, while also identifying tendencies towards new forms of control and surveillance facilitated by platforms. Topics include geopolitical and biopolitical digital sovereignty, facial recognition technologies, data divides, new methods approaches and innovative data sourcing, mobile and social media, examinations of embodied local knowledge as well as patriarchal, racist, and gendered social structures, and a broad range of field sites from Asia, Africa, and South America.